Identifying the effects of a lender of last resort on financial markets: Lessons from the founding of the fed☆ - Bernstein, Asaf; Hughson, Eric; Weidenmier, Marc D. (Journal of Financial Economics, 2010)
We use the founding of the Federal Reserve to identify the effects of a lender of last resort. We examine stock return and interest rate volatility during September and October, when markets were vulnerable because of financial stringency from the harvest. Stock volatility fell by 40% and interest rate volatility by more than 70% following the monetary regime change. The drop is insignificant if major panic years are omitted from the analysis, however. Because business cycle downturns occurred in the same year as financial crises, our results suggest that the existence of the Federal Reserve reduced liquidity risk.